2022
DOI: 10.1158/2326-6066.cir-21-0307
|View full text |Cite
|
Sign up to set email alerts
|

A Costimulatory CAR Improves TCR-based Cancer Immunotherapy

Abstract: T-cell receptors (TCR) recognize intracellular and extracellular cancer antigens, allowing T cells to target many tumor antigens. To sustain proliferation and persistence, T cells require not only signaling through the TCR (signal 1), but also costimulatory (signal 2) and cytokine (signal 3) signaling. Because most cancer cells lack costimulatory molecules, TCR engagement at the tumor site results in incomplete T-cell activation and transient antitumor effects. To overcome this lack of signal 2, we genetically… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Because of the broad expression of NGcGM3 by both solid and liquid tumors via dietary uptake in humans, there is also the potential for coadministration of anti-NGcGM3 CAR T cells with CAR T cells targeting a second antigen as a means of mitigating escape (42). Or, one could develop anti-NGcGM3 costimulatory CARs to enhance T cell receptor (TCR) based immunotherapy (43), or in the context of a parallel (p)CAR design (44). Finally, in recent years, several remote-control designs including ON-CARs (45), STOP-CARs (22), and OFF-CARs (46, 47) have been developed that could provide the means to more safely explore the translation of NGcGM3 redirected T cells to the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the broad expression of NGcGM3 by both solid and liquid tumors via dietary uptake in humans, there is also the potential for coadministration of anti-NGcGM3 CAR T cells with CAR T cells targeting a second antigen as a means of mitigating escape (42). Or, one could develop anti-NGcGM3 costimulatory CARs to enhance T cell receptor (TCR) based immunotherapy (43), or in the context of a parallel (p)CAR design (44). Finally, in recent years, several remote-control designs including ON-CARs (45), STOP-CARs (22), and OFF-CARs (46, 47) have been developed that could provide the means to more safely explore the translation of NGcGM3 redirected T cells to the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these barriers to effector cell entry, activation, expansion, and persistence, investigators have expressed molecules in T cells that may reverse these impediments to success. These include, but are not limited to, additional costimulatory signaling domains (like dual CD28 and 4-1BB, e.g., third-generation CAR T cells 47 ); direct overexpression of costimulatory molecules (e.g., CD28L or OX40L 46 ) to supply local “signal 2” in trans; and chemotactic factors and proinflammatory cytokines 65 to reduce the impact of inhibitory signals such as PDL1 50 or TGF-β 66 . Some of these approaches have now been tested clinically.…”
Section: Cellular Therapies For Solid Tumorsmentioning
confidence: 99%
“…Furthermore, several studies demonstrated the beneficial effects of combining a transgenic TCR with a non-classical, modified CAR [ 205 , 206 , 207 ]. In vivo experiments, for example, displayed that expansion and efficacy of NY-ESO-1 TCR-transduced T cells can be enhanced through co-expression of scFv-lacking 4-1BBζ CAR [ 205 ].…”
Section: Part Ii—a Change In Perspective: From “Tcr Versus Car” To “T...mentioning
confidence: 99%
“…In this regard, it was hypothesized that the CAR, albeit not engaging any target antigen, induced a certain trans co-stimulation, thereby enhancing transgenic TCR signaling. Another study demonstrated that the serial killing potential and in vivo anti-tumor response through both native or transgenic TCR was increased by co-expression of CD19 CARs with 4-1BB co-stimulation but lacking the CD3ζ signaling domain [ 207 ].…”
Section: Part Ii—a Change In Perspective: From “Tcr Versus Car” To “T...mentioning
confidence: 99%